2021
DOI: 10.1111/pace.14158
|View full text |Cite
|
Sign up to set email alerts
|

Short‐period temporal repolarization dispersion in subjects with atrial fibrillation and decompensated heart failure

Abstract: Background/objectives The association between chronic heart failure (CHF) and permanent atrial fibrillation is very frequent. The repolarization duration was already found predictive for atrial fibrillation. Aim of this study was to evaluate the influence of atrial fibrillation on short period repolarization variables in decompensated CHF patients. Method We used 5 min ECG recordings to assess the mean, standard deviation (SD), and normalized variance (NV) of the following variables: QT end (QTe), QT peak (QTp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…For these reasons, we believe that elevated fasting glucose level and an increase of Te mean could be also considered a simple noninvasive marker of short-period mortality in acutely decompensated patients. In previous studies, both fasting glucose [16] and Te mean [4–6] were significantly associated with short-period mortality in this kind of CHF subjects; the novelty of the present study was the evidence that these two studied variables mutually increased their predictive power. Whereas we do not know if these two variables are merely mortality risk markers or if they even have a causal role, however, the link between these two variables should be sought in the combination of frequent diabetes complications and pathophysiological CHF derangement.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…For these reasons, we believe that elevated fasting glucose level and an increase of Te mean could be also considered a simple noninvasive marker of short-period mortality in acutely decompensated patients. In previous studies, both fasting glucose [16] and Te mean [4–6] were significantly associated with short-period mortality in this kind of CHF subjects; the novelty of the present study was the evidence that these two studied variables mutually increased their predictive power. Whereas we do not know if these two variables are merely mortality risk markers or if they even have a causal role, however, the link between these two variables should be sought in the combination of frequent diabetes complications and pathophysiological CHF derangement.…”
Section: Discussionmentioning
confidence: 53%
“…In particular, the II ECG lead recordings, the same used in our study, could represent a marker of apicobasal and interventricular repolarization myocardial dispersion rather than transmural [24]. However, whatever the genesis of this parameter could be, Te remains a powerful predictive marker of total and cardiovascular mortality [4–8] and not a mere marker of sudden cardiac death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several works have proposed other markers related to repolarization variability measured from short-term ECG recordings, such as the variance normalized by the mean of QT end, QT peak or T-peak-to-T-end (Te) intervals, and have evaluated them in CHF populations. In recent studies, the mean and/or standard deviation of Te have been shown to predict 30-day mortality 58 , 59 and mortality in hospital 60 among decompensated CHF patients.…”
Section: Discussionmentioning
confidence: 99%